Advances and Challenges in Understanding MicroRNA Function in Tauopathies: A Case Study of miR-132/212 - Boscher, Emmanuelle; Hernandez-Rapp, Julia; Petry, Serena; Keraudren, Remi; Rainone, Sara; Loiselle, Andréanne; Goupil, Claudia; Turgeon, Andréanne; St-Amour, Isabelle; Planel, Emmanuel; Hébert, Sébastien S. (Frontiers in Neurology, 2020)
In the past decade, several groups have reported that microRNAs (miRNAs) can participate in the regulation of tau protein at different levels, including its expression, alternative splicing, phosphorylation, and aggregation. These observations are significant, since the abnormal regulation and deposition of tau is associated with nearly 30 neurodegenerative disorders. Interestingly, miRNA profiles go awry in tauopathies such as Alzheimer’s disease, progressive supranuclear palsy, and frontotemporal dementia. Understanding the role and impact of miRNAs on tau biology could therefore provide important insights into disease risk, diagnostics, and perhaps therapeutics. In this Perspective article, we discuss recent advances in miRNA research related to tau. While proof-of-principle studies hold promise, physiological validation remains limited. To help fill this gap, we describe herein a pure tauopathy mouse model deficient for the miR-132/212 cluster. This miRNA family is strongly downregulated in human tauopathies and shown to regulate tau in vitro and in vivo. No significant differences in survival, motor deficits or body weight were observed in PS19 mice lacking miR-132/212. Age-specific effects were seen on tau expression and phosphorylation but not aggregation. Moreover, various miR-132/212 targets previously implicated in tau modulation were unaffected (GSK-3beta, Foxo3a, Mapk1, p300) or, unexpectedly, reduced (Mapk3, Foxo1, p300, Calpain 2) in miR-132/212-deficient PS19 mice. These observations highlight the challenges of miRNA research in living models, and current limitations of transgenic tau mouse models lacking functional miRNA binding sites. Based on these findings, we finally recommend different strategies to better understand the role of miRNAs in tau physiology and pathology.